The spatial logic of social struggle : a Bourdieuian topology - Fogle, Nikolaus, 1981- (Lexington Books, 2011)
This is the first work to explicitly target Bourdieu's philosophy of space as a basic organizing force for his social theory. It draws together his work on both social space and physical space, and it applies the logic that binds them together to problems of architecture and urban development.